A new model of water-lubricated rubber bearings for vibration analysis of flexible multistage rotor systems. (4th August 2015) - Liu, Shibing; Yang, Bingen
Abstract: Flexible multistage rotating systems that are supported or guided by long water-lubricated rubber bearings (WLRBs) have a variety of engineering applications. Vibration analysis of this type of machinery for performance and duality requires accurate modeling of WLRBs and related rotor–bearing assemblies. This work presents a new model of WLRBs, with attention given to the determination of bearing dynamic coefficients. Due to its large length-to-diameter ratio, a WLRB cannot be described by conventional pointwise bearing models with good fidelity. The bearing model proposed in this paper considers spatially distributed bearing forces. For the first time in the literature, the current study addresses the issue of mixed lubrication in the operation of WLRBs, which involves interactions of shaft vibration, elastic deformation of rubber material and fluid film pressure, and validates the WLRB model in experiments. Additionally, with the new bearing model, vibration analysis of WLRB-supported flexible multistage rotating systems is performed through use of a distributed transfer function method, which delivers accurate and closed-form analytical solutions of steady-state responses without discretization.